Cost-effectiveness of angiotensin-converting enzyme inhibitors versus angiotensin II receptor blockers as first-line treatment in autosomal dominant polycystic kidney disease. (3rd July 2017) - Clark, L. A.; Whitmire, S.; Patton, S.; Clark, C.; Blanchette, C. M.; Howden, R.
Abstract: Background: Autosomal dominant polycystic kidney disease (ADPKD) is a rare kidney disorder impacting ∼1:2, 500 individuals among the general US population. Hypertension is a significant predictor of ADPKD progression, and a risk factor for development of cardiovascular disease (CVD), the most common cause for mortality among ADPKD patients. Angiotensin-converting enzymes inhibitors (ACE-I) are widely used as first-line treatment in ADPKD for the management of hypertension. However, their cost-effectiveness relative to other hypertensive medications, such as angiotensin II receptor blockers (ARB), has never been assessed. Objective: To determine if ARB are more cost-effective than ACE-Is as first-line treatment in ADPKD. Methods: A Markov-state decision model was constructed for estimation of cost and outcome benefits in hypertensive ADPKD patients. Transition probabilities were extrapolated from a retrospective cohort study comparing chronic kidney disease (CKD) stage transitions in ADPKD patients. Annual pharmaceutical costs per average daily dose per CKD stage were extracted from a US healthcare claims database. Median total healthcare costs per CKD stage or transplant were extracted from the published literature. The time horizon was set to 30 years, with 1-year duration to cycle shift. A cost-effectiveness analysis was conducted to estimate the incremental cost-effectiveness ratio (ICER) of ACE-I vs ARB per additional year of prevented transplant and/or death. A one-way probabilistic sensitivity analysis was conducted, with 10% variation in probabilities and cost. Results: Total annual healthcare costs accrued after 30 years among ADPKD patients taking ACE-Is was estimated to be $3, 505, 028.41, compared to ARB at $3, 644, 327.65. Life expectancy was increased by 1.39 years among patients taking ACE-I. Approximate 10-year survival in patients taking ACE-Is was 47% compared to ARB at 34%. Conclusions: ACE-I dominated ARB and displayed greater cost-effectiveness due to lower cost and increased capacity to prolong years of life without transplant or death among hypertensive ADPKD patients. This model strengthens the value of ACE-I over ARB as first-line treatment for hypertension management in ADPKD patients.